The role of gut microbiota dysbiosis in drug-induced brain injury: mechanisms and therapeutic implications - Jinghui Zhai; Yue Zhang; Shuyue Ma; Yingli Zhang; Miao Jin; Huiyu Yan; Sixi Zhang; Sixi Zhang (Frontiers in Cell and Developmental Biology)
Drug-induced brain injury (DIBI) results from toxicity, interactions or misuse and is increasingly linked to gut-microbiota dysbiosis operating via the gut–brain axis. Disturbed microbial balance drives three core mechanisms—oxidative stress, neuroinflammation and metabolic dysfunction—leading to blood–brain barrier leakage, neuronal loss and cognitive impairment; antibiotics, antineoplastics and psychoactive drugs further promote bacterial translocation and systemic inflammation. Microbial metabolites and neurotransmitters also mediate post-injury anxiety and depression. Restoring microbial equilibrium with probiotics, prebiotics or microbiota transplantation attenuates these pathways and offers a promising therapeutic strategy for DIBI.